2005
DOI: 10.1080/10413200500313503
|View full text |Cite
|
Sign up to set email alerts
|

Post-Exercise Affect: The Effect of Mode Preference

Abstract: It has been suggested that the performance of preferred modes of exercise will serve to maximize the affective response to exercise. Support has come from work that has shown the effect of exercise on affect to be mediated by enjoyment. However, there is a need to compare modes of exercise that differ in preference and enjoyment, yet are similar in intensity, duration and muscle group. This experiment was designed to achieve this aim. Thirty-four college-aged women completed 20 minutes of exercise on high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…As a consequence, they may not have benefited as much with respect to relaxation and mindfulness. Such reasoning is in line with previous research indicating that physical exercise has the highest potential for enhancing mental health when personal preferences are accounted for (Asztalos et al, 2012;Berger & Owen, 1992;Miller, Bartholomew, & Springer, 2005). However, as we have not directly measured the effectiveness of the relaxation training, this issue needs to be resolved in future research.…”
Section: Regular Aerobic Exercise Increases Mindfulnesssupporting
confidence: 55%
“…As a consequence, they may not have benefited as much with respect to relaxation and mindfulness. Such reasoning is in line with previous research indicating that physical exercise has the highest potential for enhancing mental health when personal preferences are accounted for (Asztalos et al, 2012;Berger & Owen, 1992;Miller, Bartholomew, & Springer, 2005). However, as we have not directly measured the effectiveness of the relaxation training, this issue needs to be resolved in future research.…”
Section: Regular Aerobic Exercise Increases Mindfulnesssupporting
confidence: 55%
“…Still, other studies and older experimental research have found that exercise-enhanced affective states (i.e., above baseline levels) do generally persist for three to four hours. 27,85,87 Our naturalistic data suggests that this might not necessarily be the case, or rather, that it may be relative to positive affect levels achieved postactivity. Our findings and those of others, for example, 85 seem to support propositions that the effect of physical activity can last, but that it is relative, variable, and diminishes over time.…”
Section: Discussionmentioning
confidence: 98%
“…27,85,87 Our naturalistic data suggests that this might not necessarily be the case, or rather, that it may be relative to positive affect levels achieved postactivity. Our findings and those of others, for example, 85 seem to support propositions that the effect of physical activity can last, but that it is relative, variable, and diminishes over time. 19 Another aim of this investigation was to clarify the relationship between the perceived intensity of physical activity and positive affect, doing so in natural physical activity environments over a 2-week period.…”
Section: Discussionmentioning
confidence: 98%
“…Ten positive (e.g., interested, proud, alert) and ten negative (e.g., distressed, irritable, upset) items were assessed on a five-point scale ranging from 1 (very slightly or not at all) to 5 (extremely). Studies have shown the PANAS to have acceptable psychometric properties (see Miller, Bartholomew, & Springer, 2005;Watson et al, 1988). In the present study, Cronbach alphas of .81 and .83 were obtained for positive affect and negative affect, respectively.…”
Section: Methodsmentioning
confidence: 57%